CMOS image sensor based physical unclonable function for smart phone security applications - Cao, Yuan (2015)
Recent years have seen the rapid growing market of smart phones. At the same time, pirated, knockoff or refurnished phones have also flooded into the worldwide market and inflicted great loss on the mobile phone industry. Existing anti-counterfeiting, authentification and identification methods, which rely on the verification of the IDs stored in the phone memory, are vulnerable to attack. This paper presents a new CMOS image sensor based physical unclonable function (PUF) for smart phone identification and anti-counterfeiting. The proposed PUF exploits the intrinsic imperfection during the image sensor manufacturing process to generate the unique signatures. With the proposed differential readout algorithm for the pixels of the fixed pattern noise, the effects of power supply and temperature variations are suppressed. Simulations on a typical 3-T CMOS image sensor in GF 65nm CMOS technology show that the proposed PUF can generate robust and reliable challenge-response pairs with an uniqueness of 50.12% and a reliability of 100% at temperature varying from 0°C to 100°C and supply voltage variation of ±16.7%.